The Lius of Shanghai - Cochran, Sherman, 1940- (Harvard University Press, 2013)
From the Sino-Japanese War to the Communist Revolution, a cache of letters from one of China's prominent families, the Lius of Shanghai, sheds light on a tumultuous era. Sherman Cochran and Andrew Hsieh show how the family confronted war, civil unrest, and social upheaval, and how--in the midst of it all--they built a vast business empire.